Sensitive Enzymatic Assay for Glucose Determination in Natural Waters - Cavari, B. Z. (1977)
A new enzymatic method for glucose determination is described. It allows measurement of glucose concentration as low as 10(-7) M. Such sensitivity makes this method particularly appropriate for estimation of glucose in natural-water bodies, generally without prior concentration or extraction. The method is based on the reaction between glucose and adenosine 5′-triphosphate, catalyzed by hexokinase to form glucose-6-phosphate. The amount of adenosine 5′-triphosphate consumed in this reaction, which is directly proportional to the amount of glucose present in the sample, is measured by the luciferin-luciferase assay. The optimal conditions for glucose determination by this method have been defined as follows: 20 min of incubation at 30°C, magnesium concentration of 10(-3) M, and pH in the range of 7.5 to 10.5. The specificity of the assay to different carbohydrates has also been studied. Recovery of known amounts of glucose added to Lake Kinneret water was in the range of 80 to 114%. Application of this method is demonstrated in eight monthly profiles of the glucose content in Lake Kinneret.